2022
DOI: 10.14348/molcells.2022.2032
|View full text |Cite
|
Sign up to set email alerts
|

Neural and Genetic Basis of Evasion, Approach and Predation

Abstract: Evasion, approach and predation are examples of innate behaviour that are fundamental for the survival of animals. Uniting these behaviours is the assessment of threat, which is required to select between these options. Far from being comprehensive, we give a broad review over recent studies utilising optic techniques that have identified neural circuits and genetic identities underlying these behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Predation, especially of another living prey, involved physical and mental competitions between predator and prey that was a matter of live and death. Using food pellets or live crickets, much has been learned about the attacking and consuming phases of predation, including the circuit mechanisms of several nuclei such as superior colliculus (SC), zona incerta (ZI), periaqueductal gray (PAG), the central nucleus of the amygdala (CeA), the lateral hypothalamus (LH), the mesencephalic locomotor region (MLR), the reticular formation, and spinal premotor neurons (Zhao et al 2023;Park et al 2022). However, the pursuit phase, which is also critical for successful predation, is relatively poorly understood.…”
Section: Investigation Of Predatory Pursuit In Laboratory Micementioning
confidence: 99%
“…Predation, especially of another living prey, involved physical and mental competitions between predator and prey that was a matter of live and death. Using food pellets or live crickets, much has been learned about the attacking and consuming phases of predation, including the circuit mechanisms of several nuclei such as superior colliculus (SC), zona incerta (ZI), periaqueductal gray (PAG), the central nucleus of the amygdala (CeA), the lateral hypothalamus (LH), the mesencephalic locomotor region (MLR), the reticular formation, and spinal premotor neurons (Zhao et al 2023;Park et al 2022). However, the pursuit phase, which is also critical for successful predation, is relatively poorly understood.…”
Section: Investigation Of Predatory Pursuit In Laboratory Micementioning
confidence: 99%
“…Typically, successful preying consists of a series of sequential actions, including searching, pursuing, attacking and consuming (Comoli et al 2005;Galvin et al 2021). The neural mechanisms of attack and consumption have been extensively studied in recent years in mice, a mammalian model commonly used in laboratories (Zhao et al 2023;Park et al 2022). However, much less is known about the pursuit process, which can be both mentally and physically challenging for the hunter when facing a eeing prey (Alexander et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(Moore and Biewener 2015;Holmgren et al 2021;Hayden et al 2011). Using food pellets or live crickets, much has been learned about the attacking and consuming phases of predation in mice, including the circuit mechanisms of several nuclei such as superior colliculus (SC), zona incerta (ZI), periaqueductal gray (PAG), the central nucleus of the amygdala (CeA), the lateral hypothalamus (LH), the mesencephalic locomotor region (MLR), the reticular formation, and spinal premotor neurons(Zhao et al 2023;Park et al 2022). However, the pursuit phase, which is also critical for successful predation, is relatively poorly understood.…”
mentioning
confidence: 99%
“…Also, the ventral periaqueductal gray (vPAG), which receives a strong input from the MPA 26 , 27 , is well known to be involved in modulating approaching (fight) or avoiding (flight) behaviors 28 , 29 and hunting behaviors 30 , 31 . Recent studies have revealed that MPA projections to the vPAG mediate novelty seeking, exploration, hunting behaviors, and approach to a variety of targets 32 34 .…”
Section: Introductionmentioning
confidence: 99%